2021
DOI: 10.1097/wco.0000000000000964
|View full text |Cite
|
Sign up to set email alerts
|

New developments in myotonic dystrophies from a multisystemic perspective

Abstract: Purpose of reviewThe multisystemic involvement of myotonic dystrophies (DMs) intricates disease monitoring, patients’ care and trial design. This update of the multifaceted comorbidities observed in DMs aims to assist neurologists in the complex management of patients and to encourage further studies for still under-investigated aspects of the disease.Recent findingsWe reviewed the most recent studies covering pathogenesis and clinical aspects of extra-muscular involvement in DM1 and DM2. The largest body of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
0
1
0
2
Order By: Relevance
“…It has been previously reported that both DM1 and DM2 patients are at a higher risk of developing different forms of cancer [24]. D’Ambrosio et al .…”
Section: Cancer Riskmentioning
confidence: 97%
“…It has been previously reported that both DM1 and DM2 patients are at a higher risk of developing different forms of cancer [24]. D’Ambrosio et al .…”
Section: Cancer Riskmentioning
confidence: 97%
“…Bei den myotonen Dystrophien, den häufigsten autosomal dominant vererbten Muskelerkrankungen im Erwachsenenalter, unterscheidet man zwischen der myotonen Dystrophie Typ 1 (Curschmann-Steinert, DM1) und der proximalen myotonen Myopathie (PROMM, DM2; [ 33 ]). Die DMs zählen zu den sog.…”
Section: Myotone Dystrophienunclassified
“…Bei der DM1 lässt sich von der juvenilen und adulten Form auch eine kongenitale Ausprägung mit pränatalem Symptombeginn bzw. ersten Symptomen im Säuglingsalter abgrenzen (generalisierte Schwäche, insuffiziente Ernährung und Atmung, Hypotonie, kognitive und motorische Entwicklungsverzögerung; [ 33 , 46 ]).…”
Section: Myotone Dystrophienunclassified